Peran Kualitas Layanan dan Harapan Pelanggan terhadap Kepuasan melalui Nilai yang Dirasakan - Siregar, Izza Nur Lathifa; Ravenska, Nanda; Fitriani , Laksmi; Tindaon, Susi Susanti (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: Customer satisfaction is a critical benchmark in assessing the performance of state-owned enterprises (SOEs) as it represents public trust and long-term service sustainability. In the electricity sector, performance is measured not only by technical indicators but also by the ability to fulfill customer expectations and deliver perceived value. Methodology/Approach: The research employed a quantitative explanatory design, surveying 249 customers of PLN UP3 Bandung who had used the contact center service within the last six months, selected using purposive sampling. Data validity and reliability were tested with SPSS, while hypothesis testing and structural modeling were conducted using SEM-PLS with SmartPLS. Results/Findings: The analysis demonstrates that service quality has a strong and significant influence on perceived value and satisfaction (0.688). Customer expectations also positively affect perceived value (0.241). Moreover, perceived value mediates the influence of both variables on customer satisfaction, with a path coefficient of 0.823. These findings led to the formulation of five strategic initiatives aimed at strengthening customer interaction and improving satisfaction levels at PLN UP3 Bandung. Conclusions: The study concludes that enhancing service quality and aligning with customer expectations directly and indirectly increases satisfaction through perceived value. Strengthening perceived value contributes to customer loyalty, trust, and sustainable service delivery. Limitations: The study is limited to one PLN regional unit and a short data collection period. Contribution: This research provides practical insights for PLN in optimizing service strategies and enriches academic discussions on the mediating role of perceived value in shaping satisfaction.